I am Abraham Lincoln - Meltzer, Brad.; Eliopoulos, Christopher (New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
Follows Lincoln from his childhood to the presidency, including the Civil War and his legendary Gettysburg Address.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- Politics and government -- 1861-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; United States -- History -- Civil War, 1861-1865.